The Effect of Using Comic Strips on The Eighth Grade Students' Narative Writing Achievement at SMP Negeri 5 Jember - Martages, Ika Fitriani; Suharjito, Bambang; Santihastuti, Asih (Jurnal Edukasi, 2017)
The aim of this research was to investigate whether or not there was a significant effect of using Comic Strips on the eighth grade students’ narrative writing achievement at SMP Negeri 5 Jember. The research design used was quasi-experimental research with post-test only design. The respondent of the research was chosen by using cluster random sampling. Two of the seven classes were selected as the experimental group and the control group. Through a lottery, class VIII-F was chosen as the experimental group and class VIII-E was chosen as the control group. The data was selected by writing test. Then, the data collected were analyzed by using independent sample t-test. Based on the result of the posttest scores, the mean score writing post-test in experimental group was 76.8000 while the mean score of control group was 70.5156. Moreover, based on the output of Independent sample t-test, the value of sig column of Lavene’s test was 0.020 and this value was lower than 0.05. It indicated that the result of t-test analysis was significant. It meant that the result of this research proved that the use of Comic Strips significantly affected the eighth grade students’ narrative writing achievement at SMP Negeri 5 Jember. It can be seen, especially, from the content and language use. Keywords : Writing, Writing Achievement, Comic Strips, Media